PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN KEGIATAN DASAWISNA DI DESA TAPUNG JAYA KECAMATAN TANDUN KABUPATEN ROKAN HULU TAHUN 2021 - Farhana, Nur Arsy; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The village government plays a role in facilitating the community and providing good direction to the community regarding the development and empowerment goals that will be implemented. The community plays a role in contributing thoughts, energy and property for the success of empowerment and development. The village government plays a role in implementing Dasawisma activities through its role as Facilitator, Regulator and Dynamisator. The problem in this research is that the Tapung Jaya village government is not optimal in carrying out its role as village government.The aim of this research is to determine the role of the Tapung Jaya village government in optimizing the village community empowerment program through dasawisma in 2021 and to determine the supporting and inhibiting factors in carrying out its role as village government referring to the theory of the role of village government according to Ryas Rasyid, 2010, namely the role of government as Facilitator, Regulator And Dynamisator. This research is descriptive qualitative research with the main data sources being primary data and secondary data. The data collection techniques used were interview and documentation techniques. This data analysis technique is Data Reduction, Data Presentation and Conclusion Drawing. The results of this research are that the role of the Tapung Jaya village government as the main driver in empowerment activities carried out by the Tapung Jaya Village PKK is not yet optimal, such as a lack of funds and other infrastructure such as skills training, participation and land to create dasawisma gardens and the existence of inhibiting factors in carrying out its role. Government in Tapung Jaya Village, Tandun District, Rokan Hulu Regency. Keywords: Facilitator, Regulator and Dynamisator